Korelasi Antara Pemahaman Akidah dengan Etika Digital Siswa Di SD Plus Al Ishlah Bondowoso - Amaliatul Fitriyah; Nurul Hayati; Sumiyati; Safitrianingsih; Benny Prasetiya (Education Reserach Center, 2025)
This study aims to empirically examine the effect of aqidah (Islamic creed) understanding on students’ digital ethics at SD Plus Al Ishlah Bondowoso. The research employed a quantitative approach with an explanatory research design. The study population comprised all 80 students of SD Plus Al Ishlah Bondowoso, who were simultaneously designated as the sample through a total sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through simple linear regression using SPSS version 26. The findings indicate that aqidah understanding has a positive and statistically significant effect on students’ digital ethics, as evidenced by a regression coefficient of 0.815 and a significance value of p < 0.05. The coefficient of determination (R²) of 0.505 demonstrates that aqidah understanding accounts for 50.5% of the variance in students’ digital ethics. These results underscore that aqidah education functions not only as a theological foundation but also plays a strategic role in shaping students’ ethical behavior in the digital era. Therefore, the integration of aqidah education with digital literacy should be further strengthened to foster character development and digital ethics among students in Islamic elementary schools.